1977
DOI: 10.1177/031289627700200202
|View full text |Cite
|
Sign up to set email alerts
|

Share Capitalization Changes, Information, And the Australian Equity Market

Abstract: Bonus issues, share splits and rights issues are studied in a replication and extension of the classic Fama, Fisher, Jensen and Roll study. On the Melbourne exchange, each category on average is associated with positive abnormal returns. However, the market does not appear to value bonuses or splits in their own right: prices appear to reflect the information released in the capitalization changes (and associated events). For example, share splits which were not accompanied by effective dividend increases did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 10 publications
2
23
0
2
Order By: Relevance
“…Therefore, on average, the bonus proposals raise positive CARs around the announcement date. That the announcement of bonus proposals, on average, has a positive effect on China's stock prices coincides with the evidence of Ball, Brown, and Finn (1977) for Australian stock prices. The CARs of an "Overall" portfolio are by construction an aggregate of different sizes of bonus issues.…”
Section: A-shares Return Behavior Around the Announcement Of Bonus Prsupporting
confidence: 67%
“…Therefore, on average, the bonus proposals raise positive CARs around the announcement date. That the announcement of bonus proposals, on average, has a positive effect on China's stock prices coincides with the evidence of Ball, Brown, and Finn (1977) for Australian stock prices. The CARs of an "Overall" portfolio are by construction an aggregate of different sizes of bonus issues.…”
Section: A-shares Return Behavior Around the Announcement Of Bonus Prsupporting
confidence: 67%
“…Empirical work (particularly in the United States) has shown that the market generally reacts positively to the announcement of a bonus issue/stock dividend (see, e.g., United States- Foster & Vickrey, 1978;Grinblatt, Masulis, & Titman, 1984;McNichols & Dravid, 1990;Rankine & Stice, 1997a, 1997bWoolridge, 1983;Australia-Ball, Brown, & Finn, 1977, Canada-Masse, Hanrahan, & Kushner, 1997New Zealand-Anderson, Cahan, & Rose, 2001;Sweden-Lijleblom, 1989). The current paper extends the earlier work of Ball et al (1977) by investigating the impact of Australian company bonus issues on share prices around announcement dates using daily return data for the period from January 1992 to December 2000.…”
Section: Introductionmentioning
confidence: 82%
“…Pettit (1972Pettit ( ) 1967Pettit ( -1969 dönemlerini kapsayan ve 135 firma üzerinde yapmış olduğu çalışmada kâr payı değişiklikleri sonucu ortaya çıkan duyurularının hisse senedi fiyatlarına etkisini incelemiş, kâr payı değişim duyurularının önemli bilgiler içerdiğini ve piyasanın bilginin hisse senetleri fiyatlarına dâhil edilmesinde etkili olduğunu gözlemlemiştir. Ball, Brown ve Finn (1977) 1960-1969 yılları arasında aylık hisse senedi verilerini kullanarak hisse senetlerinin bedelsiz olması ya da bölünmesi gibi duyuruların hisse senedi fiyatlarına etkisini incelemiştir. Araştırma bulgularına göre, kâr payı dağıtım duyurularının hisse senetleri fiyatlarında istatistiksel olarak etkisi olmadığı gözlemlenmiştir.…”
Section: Literatür İncelemesiunclassified